Spinal cord injuries in the absence of post-traumatic radiographic anomalies (SCIWORA): the traumatic moment between patient anterior state and efficient/concurrent causes of injury - Basile, Giuseppe; Fozzato, Stefania; Petrucci, Quirino Alessandro; Gallina, Mario; Accetta, Riccardo; Passeri, Alberto; Bianco Prevot, Luca; Marinelli, Enrico (Acta Biomedica Atenei Parmensis, 2023)
Background and aim:Spinal Cord Injury without Radiographic Abnormality (SCIWORA) represents acute traumatic myelopathy in the absence of instrumental evidence of fractures and/or dislocations of the cervical vertebrae. Methods:In this article we present 4 cases of SCIWORA that came to our observation and the medico-legal implications associated with them.Results:In defining the compensation in the context of a private accident policy for traumatic pathologies of the spinal cord, an in-depth medical-legal assessment is essential, based on an accurate examination of the health documentation including the instrumental investigations performed, the anamnesis and an accurate evaluation of the trauma dynamic. The paraphysiological deterioration of organ-tissue structures, identifiable in the concept of "natural variability of biological risk", should be included in the same definition of insured risk by age group, with the consequence that physical conditions that fall within the physiological or paraphysiological definitions, although potentially contributing to injury, do not necessarily exclude compensation. A different concept dominates the variability of the compensation according to a paraphysiological pre-existing condition. The two arguments therefore call for thorough consideration of both the paraphysiological contributing causes of injury and/or impairment as necessarily subject to a preliminary study, which through the clinical and instrumental investigation method, will define the perimeter of functionality.